Comparative evaluation of the chlorhexidine and cinnamon extract as ultrasonic coolant for reduction of bacterial load in dental aerosols - Kunal Sunder Sethi; Alefiya Mamajiwala; Swapna Mahale; Chetan Purushottam Raut; Prerna Karde (Wolters Kluwer Medknow Publications, 2019)
Background: Ultrasonic instruments generate aerosols with significantly greater number of bacteria. Preprocedural mouthrinses or chemotherapeutic coolants are used for the reduction of bacterial load in dental aerosols. The use of chlorhexidine as an ultrasonic coolant has been well established. However, this application has not yet been investigated for cinnamon extract which is known to have antibacterial and anti-inflammatory properties in vivo. Aim: The aim of this study is to compare and evaluate the efficacy of chlorhexidine and cinnamon extract as an ultrasonic coolant in reduction of aerosol contamination and biofilm formation during ultrasonic scaling in comparison with the distilled water (DW). Materials and Methods: Sixty patients diagnosed with moderate-to-severe gingivitis were randomly divided into three groups of twenty patients each undergoing ultrasonic scaling. For Group I, chlorhexidine was used as an ultrasonic coolant; for Group II, cinnamon extract was used; and Group III was served as control where DW was used. The aerosols from ultrasonic units were collected on two blood agar plates at three different positions. Both the plates from each position were incubated aerobically for 48 h. The total number of colony-forming units were counted as mean ± standard deviation and statistically analyzed. In addition, biofilm sampling of dental unit waterlines (DUWLs) was also done to evaluate the effect of these antimicrobials. Apart from microbial examination, clinical parameters such as plaque index and gingival index were also evaluated at baseline and 1-month follow-up. Results: Chlorhexidine and cinnamon both were equally effective (P > 0.05) in reducing the bacterial count in aerosols and biofilm in DUWL as compared to DW when used as ultrasonic cooling agent. Conclusion: Both cinnamon and chlorhexidine used as an ultrasonic device coolant through DUWLs effectively helped in the reduction of bacterial count in dental aerosols.